HOTS Skills in Arabic Learning: What are the Opportunities and Challenges in The Digital Age? - Fitri Alrasi; Mahyudin Ritonga; Muhammad Jalel Ritonga; Apip Muda Ritonga (UIN Mahmud Yunus Batusangkar, Indonesia, 2025)
The integration of HOTS (Higher Order Thinking Skills) into Arabic language learning is essential to prepare 21st-century students for increasingly complex global demands. This study explores the implementation of HOTS-based Arabic learning by examining the opportunities and challenges encountered in the digital era, with a specific focus on a technology-integrated Islamic boarding school context. Employing a qualitative case study approach at Thursina International Islamic Boarding School (IIBS) Malang, Indonesia, data were collected through observation, interviews, and documentation. Analysis followed the Miles and Huberman framework, encompassing data reduction, presentation, and verification, with validity strengthened through triangulation of data and sources. The findings indicate that: a) HOTS implementation in Arabic learning is highly relevant and feasible through digital platforms, yet it faces significant challenges; b) the primary opportunities include enhanced accessibility, student engagement, and global competitiveness, while the most dominant challenges stem from teachers’ limited HOTS pedagogical knowledge, uneven student Arabic proficiency, and a lack of HOTS-oriented teaching materials. This study concludes that HOTS skills, when effectively integrated with digital tools, can significantly foster globally competitive learners, provided that systemic supports are strengthened